Pengaruh Sistem Administrasi Modern, Keadilan, Akuntabilitas, dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak UMKM Kota Jambi - Eva Setiarini Damanik (Ekonomis: Journal of Economics and Business, 2021)
This study aims to examine the effect of the modern administration system, justice, accountability, and tax sanctions on the tax compliance of the MSMEs of the City of Jambi. This study uses a simple random sampling method with 100 UMKM taxpayer respondents in the city of Jambi. Data collection techniques in this study were in the form of questionnaires. The analysis used is multiple linear regression analysis using IBM SPSS (Statistical Package for Social Sciences) version 21. The results of this study indicate that the variables of modern administrative systems, justice, accountability, and tax sanctions affect the compliance of MSME taxpayers.